Lima no respondía. El fracaso del plan insurreccional planteado en México explicado en carta de Víctor Raúl Haya de la Torre a Wilfredo Rozas, fechada el 22 de septiembre de 1929 - Parodi Revoredo, Daniel (2022)
This research deals with the insurrectionary Plan proposed in Mexico by APRA leader Víctor Raúl Haya de la Torre in 1928, which obtained tenacious opposition from José Carlos Mariátegui La Chira. The Insurrectionary Plan was never carried out because Mariátegui initiated a harsh ideological polemic against Haya that distracted the other Peruvian APRA cells and prevented them from joining the revolution. Our central thesis is that Mariátegui saw his position as leader of the Peruvian left, obtained after the founding of the magazine Amauta in 1926, threatened, since the Haya Plan proposed the creation of the Partido Nacionalista Libertador, with headquarters in Mexico. This approach relegated Mariátegui and the Lima group to the background, so they began an open confrontation against APRA, which divided the Peruvian left and frustrated the insurrectionary PlanKeywords: Víctor Raúl Haya de la Torre, José Carlos Mariátegui, APRA, Haya-Mariátegui controversy, Plan de México, Partido Nacionalista Libertador.